Ketogenic diet is less effective in ameliorating depression and anxiety in obesity than Mediterranean diet: A pilot study for exploring the GUT-brain axis - Mela, Virginia; Ortiz-Samur, Nadia Suyin; Vijaya, Akshay Kumar; García-Martín, María Luisa; Bandera, Borja; Jiménez-Gálvez, Vanesa; Martínez-Montoro, José Ignacio; Gómez Pérez, Ana María; Moreno-Indias, Isabel; Tinahones-Madueño, Francisco José (Elsevier, 2025)
Obesity is associated with depressive symptoms due to biological and psychological factors. Dietary interventions, including the Ketogenic (Keto) and Mediterranean (Med) diets, impact weight loss and mental health differently. While the Keto diet promotes rapid weight loss by increasing ketone body levels, its effects on mental health, particularly in individuals with obesity, remain unclear. This exploratory pilot study explores the impact of both diets on depression and impulsiveness, focusing on the gut-brain axis. Sixty-four participants (Body Mass Index 30–45 kg/m 2 , ages 18–65) were randomly assigned to follow one of the two diets for three months. Due to attrition, 37 participants (Med n = 23; Keto n = 14) completed the study. Depression and impulsivity scores were evaluated before and after the intervention. Stool samples were collected for microbiota analysis, and faecal transplants were performed in healthy mice. Brain and serum metabolites in recipient mice were analysed using High-Resolution Magic Angle Spinning (HR-MAS) and Proton Nuclear Magnetic Resonance ( 1 H NMR) spectroscopy. The Med diet showed greater improvement in depression scores compared to the Keto diet, while the latter was associated with reductions in impulsivity (urgency subscale). However, faecal transplants from the Keto group induced anxiety-like behaviours in recipient mice, which correlated with significant microbiota and metabolite changes. The Keto group exhibited increased levels of taurine, alanine, and betaine in the brain, and threonine levels were correlated with behavioural changes. These findings suggest that the Med diet offers more consistent short-term benefits related to depressive symptoms, while the Keto diet modulated impulsivity. The animal model findings highlighted the role of diet-induced microbiota changes and metabolite alterations in the gut-brain axis.
Disponible online desde el 4 de noviembre de 2025
Keywords: Depresión mental; Obesidad; Intestinos Microbiología; Estrés (Psicología); Hábitos alimenticios; Nutrición; Dieta; Depression; Obesity; Microbiota; Keto diet; Anxiety; Mediterranean diet